HUBUNGAN SIKAP, MOTIVASI DAN PEMANFAATAN MEDIA BELAJAR DENGAN PRESTASI BELAJAR IPS PADA UPT SDI BENTENG TIMUR NO. 112 KEPULAUAN SELAYAR - Ruslan Musyafir Hadi (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to determine 1) the relationship between attitudes towards social studies student achievement UPT SDI Benteng Timur No. 122 Selayar Islands 2) the relationship between motivation and achievement of social studies students at UPT SDI Benteng Timur No. 112. Selayar Islands 3) the relationship between the use of learning media on the achievement of social studies students at UPT.SDI.Benteng.Timur.No. 112. Selayar Islands 4) The Relationship of Attitude, Motivation and Utilization of Learning Media with Social Studies Student Achievement at UPT SDI Benteng Timur No. 112. Selayar Islands. The type of research used is quantitative because it can give number symbols in stages or by calculating the frequency/amount separately from one another. This research was conducted at UPT SDI Benteng Timur No. 112 Selayar Islands. The population in this study were all students of UPT SDI 112 Selayar Islands, amounting to 25 people. the sample is taken as a whole, but if the population is greater than 100 people, then 10-15% or 20-25% of the total population can be taken. Data collection techniques using questionnaires and documentation. The data analysis technique used Pearson product moment correlation coefficient and multiple linear regression analysis. The results showed that 1) There was a significant relationship between attitudes and student achievement in class V UPT SDI Benteng Timur No.112.Selayar Islands 2) There was a significant relationship between motivation and student achievement in class V UPT SDI East Fort No. 112 Selayar Islands 3) There is a significant relationship between the use of learning media and the learning achievement of fifth grade students at UPT SDI Benteng Timur No. 112 Selayar Islands 4) There is a simultaneous significant relationship between Attitude, Motivation and Utilization of Learning Media with the learning achievement of fifth grade students of UPT SDI fort Timur No. 112 Selayar Islands.